Analysis of Complaint Management in RSUD Tugurejo - Soeyono, Aini; Zahroh Shaluhiyah, Zahroh; Arso, Septo Pawelas (Public Health Perspective Journal, 2021)
complaint is an expression of dissatisfaction with a service or product provided. Patient complaints are a source of information in improving the quality of service Patient complaints are a source of information in improving service quality and detecting deficiencies in the health care system in the hospital. The most recurring complaints at Tugurejo Hospital in 2017 - 2019 were complaints about doctor services at the Outpatient Installation and infrastructure at Tugurejo Hospital. The purpose of this study was to analyze the complaint management system for doctor services in outpatient installations and infrastructure using the Managerial Operational Technique (MOT) method. This research is a descriptive qualitative research with a case study approach. The research instrument is the researcher himself. Data collection was carried out by in-depth interviews, observation and documentation. The informants of this study were the Customer Service coordinator, the head of the household division, the head of the general division, the head of the outpatient services section, and doctors in the outpatient installation. Triangulation informants were the deputy director general and finance and deputy director of services at the Tugurejo Hospital. The results showed that the complaint management system of the tugurejo hospital in the managerial dimension, namely the strategic plan and organizational structure was good. In the leadership dimension, it was found that some leaders were not good communicators. In the staff dimension, educational backgrounds in the Customer Service unit vary. This is due to limited manpower and budget so that the hospital optimizes existing personnel. For staff training regarding hospital services it has been done but it is not specific about the handling of complaints. In the dimension of work culture, a culture of openness to complaints by doctors and not strict management is one of the consequences of recurring complaints about doctor services in outpatient installations. For the operational dimension, namely the implementation process for complaint handling has been going well. The management of change has been going well, although there are still many obstacles in its implementation. The output management needs to be improved for each unit, namely monitoring and evaluation. In the dimension of obstacles in the household subsection is the budget, for the service sector is openness to complaints and lack of firm management. For the technical dimension, the capability and information system of recording each section have not been implemented optimally.